Kodular-based learning media: Enhancing instruction on informatics education to vocational high school students - Nurhaliza, Sindi; Effendi, Noverta; Farida, Fitri (Researcher and Lecturer Society, 2025)
This study explores the development of Kodular-based learning media to enhance the quality of informatics education. The study addresses the need of more engaging learning media and better technology integration in teaching using a Research and Development (R&D) design and a modified 3D model out of the 4D development model, including defining, designing, and developing. The research involved 20 students from SMK Negeri 1 Bangkinang, employing all stages of the development model: need analysis, media development, validation, and trial to students. The defining stage revealed inappropriate teaching method uses, leading students to have less motivation in learning. Consequently, this research developed learning media, focusing on number systems material (decimal, binary, octal, hexadecimal), organized in a visually appealing and concise format. In the designing phase, the Kodular media was developed to be user-friendly, featuring quizzes, exercises, and interactive modules. Validation results showed high feasibility scores, with media experts rate on 88.57% and material experts rate on 95%. During the developing stage, a trial to students yielded a score of 4.81 out of 5, classifying the media as